How atmospheres inform urban planning practice – insights from the Tempelhof airfield in Berlin - Ulrike Mackrodt (Ambiances)
The fundamental subject matter of urban planning is urban space. However, this fact is rarely reflected in planning theory. Instead of dealing with the everyday use of urban space and its atmospheric perception, planning discourse is dominated by theories of action, which primarily focus on communication processes within planning practice. The role of urban space within these planning negotiations is often overlooked. By disregarding the feeling and sensing body/subject as being the base of any perception – including those of planning professionals – planning discourse has left out the chances of a more comprehensive understanding of how planning decisions occur. The article aims to fill this epistemological gap by applying the concept of atmospheres to the case study of the planning process for the former inner-city airfield Tempelhof in Berlin. Thereby it becomes possible to consider the impact of the – borrowing Gernot Böhme’s terminology – ‘unobtrusive obtrusiveness’ of atmospheres on the controversial planning case of Tempelhof airfield. The empirical findings – based on interview data – demonstrate how the planners’ atmospheric perception of Tempelhof airfield translates into distinctive, and more importantly, controversial planning decisions. In doing so, the article provides a basis for developing atmospheric competences, which have been absent in urban planning thus far.